Toxicity of Two Extracted Destruxin Against Palpita unionalis (Lepidoptera: Crambidae) under Laboratory and Field Conditions - M, Sabbour M. (American Journal of Chemistry, 2018)
Olive trees are subjected to attack by many insect pest species that affect yield quality and quantity. Among the most common olive pest species surveyed in Egypt is Palpita unionalis. The fungus, Metarhizium anisopliae (Metschnikoff) Sorokin produces some cyclic peptide toxins, destruxins, Destruxin which may play a role in its pathogenicity in insect pests and decreases the infestations of many harmful pests. The present study aimed to evaluate the efficacy of this two solated Destruxin (Destruxin A-760 and Destruxin A- 724) against P. unionalis under laboratory and field conditions. The results obtained showed that the LC50 of Destruxin A-760 on the third larval instars was 151 ppm. However, when Destruxin A- 724 was applied on the target pest, the LC50 reached to 185 ppm. Under field conditions, both isolated Destruxin declined the rate of infestation by P. unionalis with the least infestation in case of treatment with Destruxin A- 724 compared to untreated olive trees. The yield of harvested olive fruits increased due to treatment with isolated Destruxin the highest yield in case of trees treated with Destruxin A-760.